Enhanced dielectric properties of filled PVDF/MgO polymer nanocomposite / Adillah Nurashikin Arshad - Arshad, Adillah Nurashikin (2015)
PVDF and PVDF/MgO nanocomposite thin films (MgO loading percentages 1, 3, 5, 7, 9 and 11 .wt%) were produced by spin coating on Al-glass substrates at 1500rpm. PVDF thin films were annealed subsequently at 70°C, 90°C, 110°C, 130°C, 150°C and 170°C, and then were cooled by fast cooling (FC) and slow cooling (SC). PVDF thin films annealed at 70°C with SC resulted an increment in the dielectric constant from 10 (UNPVDF) to 14 at 1 kHz frequency with low tangent loss of 0.05 (UN-PVDF = 0.1). An increased in the resistivity value of 3.2x10⁴ Ω.cm (UN-PVDF = 2.0x10⁴ Ω.cm) was also observed. Upon incorporation of MgO nano-filler, PVDF/MgO(7%) nanocomposite thin film showed highest dielectric constant of 22 at similar frequency compared to UN-PVDF (10), with low dielectric loss (ɛ"= 0.08), as well as an increase in resistivity value in comparison to PVDF/MgO film of 1, 3, 5, 9 and 11 wt% MgO loading. Most importantly, PVDF/MgO(7%) nanocomposite thin film was found to be free from defects such as voids as evident from FE-SEM images of the films. The broad significant bonding peaks at 840 and 880 cm¯¹ as observed from the FTIR spectrum were representations of the - CH₂ and -CF₂ groups of PVDF film with an indication of high content of P-phase crystals, which contributed to an increment in the dielectric constant of PVDF/MgO(7%) nanocomposite thin films. Hence, by utilizing this two parameters, PVDF/MgO(7%) nanocomposite thin films and then annealed at 70°C with SC, resulted in the highest dielectric constant value of 27 for this study, with small increased in tangent loss of 0.13 at 1 kHz frequency. Resistivity value of annealed PVDF/MgO(7%) was also observed to increase (10.5x10⁴ Ω.cm). Thus, it was concluded that PVDF/MgO(7%) annealed at 70°C, and then cooled slow cooling was the optimized parameter conditions required for producing high dielectrics properties of PVDF nanocomposite thin films.